Proposal for a conceptual model on the role of managerial coaching on employee satisfaction and engagement - Sara Nait Slimane; Mahouat Nacer (Environment and Social Psychology, 2025)
This study develops a conceptual model based on the works of several authors in the fields of managerial coaching, employee work engagement, and job satisfaction. The model is theoretically grounded in the Job Demands–Resources (JD-R) model, Self-Determination Theory, and Social Exchange Theory (SET), providing a robust framework to explain how coaching practices shape employee attitudes. It hypothesizes that managerial coaching is positively related to employee work engagement (H1) and job satisfaction (H2). Furthermore, it proposes that work engagement mediates the relationship between managerial coaching and job satisfaction (H3), such that coaching fosters higher engagement, which subsequently enhances job satisfaction. By integrating insights from prior studies and established theoretical perspectives, this research offers a comprehensive understanding of both the direct and indirect pathways linking managerial coaching to positive employee outcomes. The findings are expected to be valuable for researchers in management science and social science, as they advance theoretical development and offer evidence-based guidance for organizational practice.